2022
DOI: 10.3390/dairy3010006
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach in the Evaluation of Dairy Camels: Using Test Day Milk and Morphometric Records

Abstract: In the case of camels, there is little data in the literature on the relationship between body building features and the evaluation of milk yield. In the last decade, a rising interest in camel milk has been observed due to its nutritional and health-promoting properties, resulting in a growing market demand. Despite the remarkable importance of camels, very little improvement in camel breeding and selection for dairy purposes has been achieved. The current study aimed to provide a practical approach to the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Furthermore, this remarkable increase in records has also been driven by recent international projects and collaborations, such Most of the records on camels came from Asia; this is not surprising considering that Asia has the second-largest Dromedary camel population globally (6). Furthermore, the intensification of Dromedary camel production has been on the increase in Asian countries (9)(10)(11), and these nations boast dedicated research centers focused on camel research (38). Similarly, Iglesias Pastrana et al (39) in their bibliometric research about camels indicated that countries with traditionally well-established camel farming are responsible for the papers with the highest academic impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this remarkable increase in records has also been driven by recent international projects and collaborations, such Most of the records on camels came from Asia; this is not surprising considering that Asia has the second-largest Dromedary camel population globally (6). Furthermore, the intensification of Dromedary camel production has been on the increase in Asian countries (9)(10)(11), and these nations boast dedicated research centers focused on camel research (38). Similarly, Iglesias Pastrana et al (39) in their bibliometric research about camels indicated that countries with traditionally well-established camel farming are responsible for the papers with the highest academic impact.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been an increase in intensive camel production in peri-urban farms, supplying milk to urban dwellers (9). The growing intensification of camel husbandry systems is determined by the increase in demand for camel milk due to its nutritional and health enhancement benefits (10). The trend towards intensification in camel husbandry is also expected to increase in the coming years due to various reasons, including climate change (11).…”
Section: Introductionmentioning
confidence: 99%